Teaching styles and student performance in conceptual and algorithmic problem solving in chemistry - Paz, Efren P. (2009)
This study investigates the relationship of teaching styles with students' performance in conceptual and algorithmic problem solving in chemistry. The teaching styles of 8 teachers were determined using the Grasha-Reichmann Teaching Style Survey for Teachers, field notes, classroom interactions, class discussion, and interviews. The survey was revised and administered to 103 public school secondary science teachers. Based on the results of the study, it was concluded that the combination of high Delegator and high Expert teaching style is effective for the development of conceptual problem-solving skills in chemistry and help students achieve a high score in both conceptual and algorithmic problem-solving in chemistry.
"April,2009."
Thesis (M.A. Chemistry Education)--University of the Philippines Diliman.
Keywords: Chemistry -- Study and teaching (Secondary) -- Philippines -- Bataan; Problem solving; Chemistry teachers -- Philippines -- Bataan; Public schools -- Philippines -- Bataan